Notification of international normalized ratio test in atrial fibrillation patients treated with warfarin via short message service: Study protocol for a randomized controlled trial - Sheibani, Reza (Electron Physician, 2017)
BACKGROUND: Atrial Fibrillation (AF) is the most common abnormal heart rhythm. AF patients usually use warfarin therapy. Safety and efficacy of warfarin are dependent on maintaining the International Normalized Ratio (INR) within the therapeutic range. OBJECTIVE: We will use a Short Message Service (SMS) to evaluate the effect of a reminder on carrying out the INR laboratory test in a timely manner. METHODS: This study (a Randomized Controlled Trial) will be done in Loghman hospital Tehran, Iran. Convenience sampling will be done and 400 AF patients that have inclusion criteria will be randomized equally to an intervention or control group. Patients in the intervention group will receive an SMS that will remind them of the INR test date. The SMS will be sent at 6 PM on the day before and 8 AM on the scheduled date but the patients of the control group will receive usual care without any SMS reminders. We will evaluate the effect of reminders on carrying out the INR test in a timely manner and maintaining the INR in the therapeutic range. Patients’ follow-up will be done via telephone conversation to identify thromboembolic events, bleeding and mortality. The data will be analyzed by IBM SPSS version 24. We will use independent samples t-test or Mann–Whitney and Chi-square tests for the analyses of outcomes. DISCUSSION: This protocol describes the randomized control trial to study the effects of the SMS reminder system on adherence to the timing of INR test in AF patients treated with warfarin. The research will also form the basis for future decision support systems for monitoring of patients who receive oral anticoagulants. TRIAL REGISTRATION: Iranian Registry of Clinical Trials (http://www.irct.ir) was used to register the trial and IRCT ID was IRCT2016052528070N1. FUNDING: This research was supported by Mashhad University of Medical Sciences.